Bridging the gap: skin for all and its impact on addressing racial inequalities in medical education - Naabil Khan (Future Healthcare Journal)
Introduction: The lack of ethnic minority representation in the medical community is vital in driving the movement towards proportionate representation in medical education. Skin For All, addresses the challenge within the UK's National Health Service by diversifying clinical descriptions to prevent potential misdiagnoses. With a focus on over 30 prevalent skin conditions, Skin For All employs accessible language and segmented information, tailoring resources for diverse user backgrounds. This initiative aims to reshape medical education and patient awareness by providing an inclusive, comprehensive resource aligned with the NHS's commitment to equitable healthcare [1]. Aim: The website aim is to raise awareness about racial disparities in medical education and clinical practice, encouraging familiarity with inclusive language in clinical skin descriptors. Skin For All also strives to normalise diverse images and language in medical curricula, supporting non-medical personnel in recognising skin conditions on diverse skin tones. Method: The methods involve utilising six diverse platforms to identify prevalent skin conditions, catering to both patients and clinicians globally. The information is sourced from reputable clinical websites and patient-focused platforms, ensuring a well-rounded perspective. Results: Since its inception in June 2023, Skin For All has gained significant traction, accumulating 6,500 page visits by December 2023, with an additional 650 page views from January 2024 to the present date. The website's impact has been acknowledged through media appearances on BBC Spotlight and LBC Radio in October 2023 [2]. Furthermore, Skin For All's integration into the Exeter University Problem Based Learning curriculum in October 2023 signifies progress towards its goal of curriculum integration. Qualitative results include presentations at the University of Osteopathy and the Public Involvement in Medical Education group linked to Exeter Medical School, showcasing increased public and student education surrounding the initiative's ethos. Discussion/conclusion: The discussion emphasises the importance of bottom-up, student-led projects like Skin For All in promoting diversity in medical school curricula. Other methods of change in medical education include calls for cases involving ethnic minority patients, diverse images, and reading lists [3]. For patients, raising awareness through public health groups and media appearances is vital in normalising diversity within the medical sphere [4]. While further research is required to present concrete outcomes, Skin For All's prominence in medical academia is evident through its cross-university presentations, user count, and PBL integration. In conclusion, Skin For All serves as a testament to the importance of inclusive healthcare, actively addressing the underrepresentation of ethnic minorities in medical education. Its multifaceted approach aims to reshape medical education and patient outcomes, aligning with the NHS's commitment to equitable healthcare.